Dual in Slovene: on the 100th anniversary of the first study on Slovene dual (Tesnière 1925) - Jakop, Tjaša (Slavia Centralis, 2025)
The year 2025 marks the 100th anniversary of the publication of the first systematic work on the Slovene dual. In 1925, the Frenchman Lucien Tesnière published the Linguistic Atlas of the Dual (Atlas linguistique pour servir à l’étude du duel en slovène) with an accompanying monograph on dual forms in Slovene, Les formes du duel en slovène. In 2008, another researcher of the Slovene dual, Tjaša Jakop, published two monographs dedicated to this typically Slovene category, namely Dvojina v Slovenskih Narečjih and The Dual in Slovene Dialects. This article discusses these and other well-known works dealing with the dual in Slovene, provides typical examples of its use, and offers final conclusions.
Keywords: morphology; dual number; the 16-th century Slovene literary standard; Slovene dialects; Lucien Tesnière; Tjaša Jakop